1976
DOI: 10.1083/jcb.71.2.624
|View full text |Cite
|
Sign up to set email alerts
|

The light-harvesting chlorpohyll-protein complex of photosystem II. Its location in the photosynthetic membrane.

Abstract: We have investigated the structure of the photosynthetic membrane in a mutant of barley known to lack a chlorophyll-binding protein. This protein is thought to channel excitation energy to photosystem II, and is known as the "light-harvesting chlorophyll-protein complex." Extensive stacking of thylakoids into grana occurs in both mutant and wild-type chloroplasts. Examination of membrane internal structure by freeze-fracturing indicates that only slight differences exist between the fracture faces of mutant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…Indirect evidence, based on the loss of EFs particles in photosystem II mutants (15,23), further indicated that EFs panicles contain the reaction centre ofphotosystem II. Examination of a barley mutant lacking Chl b and LHCII, in which the EFs particles were reduced in size, led to the suggestion that EFs particles normally contain LHCII, the major light-harvesting chlorophyll-protein of thylakoids (16). This model was extended by AR-MOND et al (6), who followed the greening of pea grown under intermittent light and then transferred to continuous light.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Indirect evidence, based on the loss of EFs particles in photosystem II mutants (15,23), further indicated that EFs panicles contain the reaction centre ofphotosystem II. Examination of a barley mutant lacking Chl b and LHCII, in which the EFs particles were reduced in size, led to the suggestion that EFs particles normally contain LHCII, the major light-harvesting chlorophyll-protein of thylakoids (16). This model was extended by AR-MOND et al (6), who followed the greening of pea grown under intermittent light and then transferred to continuous light.…”
Section: Introductionmentioning
confidence: 86%
“…Their model indicates that LHCII extends into the thylakoid lumen and presumably forms part of the 4 subunits of the tetrameric ESs particle. The Chl b-less barley mutant contains tetrameric ESs panicles (16,22), but they are significantly smaller than those of wild type thylakoids. A re-examination of this mutant led to the proposal that LHCII is located in PFs particles, and that the reduction in EFs and ESs particle size was postulated to be due to the loss of other Chl a/b-binding proteins (22).…”
Section: Introductionmentioning
confidence: 99%
“…The complementary protoplasmic fracture face of the stacked membranes (PFs) contains the ;8-nm LHCII particles (Miller et al, 1976;Simpson, 1979). The protoplasmic fracture face of the unstacked membranes is distinguished on the basis of its slightly larger asymmetric ;10-nm photosystem I particles (Simpson, 1982).…”
Section: The Photoprotective Structural Change Remodels the Psii-lhcimentioning
confidence: 99%
“…These supercomplexes represent the basic functional units of the PSII-LHCII macrostructure and can be supplemented by an additional three to four loosely attached LHCII trimers (L-trimers) Dekker et al, 1999). These C 2 S 2 and C 2 S 2 M 2 PSII-LHCII supercomplexes can also further become arranged into higher-order semicrystalline arrays (Miller et al, 1976;Staehelin, 1976;Boekema et al, 2000;Kirchhoff et al, 2007a;Daum et al, 2010). In contrast with PSII, photosystem I and the ATP synthase complex are mainly confined to the nonappressed stromal lamellae regions of the thylakoid membrane and the grana end membranes (reviewed in Hankamer et al, 1997;Dekker and Boekema, 2005;Daum et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the freeze fracture technique has been introduced to the study of the particulate structure of the thylakoid membrane (1,2,4,17,23,24). The small particles, presumably the PS-I complexes, are embedded in the thylakoid membrane in a manner that they are localized more externally to protrude partially into the partition side, that is, the outer surface side (1, 2, 4, 17), or to have a wider frontage on this side (23,24).…”
Section: Discussionmentioning
confidence: 99%